Local switching in SBN:Ni single crystals with various initial domain states. (12th March 2018) - Shikhova, V. A.; Fedorovyh, V. V.; Turygin, A. P.; Gimadeeva, L. V.; Chezganov, D. S.; Vlasov, E. O.; Alikin, D. O.; Ivleva, L. I.; Kholkin, A. L.; Shur, V. Ya.
ABSTRACT: We present the results of experimental study of the local switching in single crystals of relaxor ferroelectric Ni-doped strontium barium niobate with various initial domain states using conductive tip of scanning probe microscope. We investigated the domain growth in as-grown domain structure and initial domain states created by: (i) scanning by biased tip, (ii) in-field cooling, and (iii) scanning by electron beam. The dependences of effective domain radius on the voltage and pulse duration were derived. The shape factor, domain wall mobility, and start voltage were revealed. The obtained results can be used for the domain engineering in ferroelectrics.